Characterization and performance investigation of metallic oxides based nanofluids in compound parabolic concentrating solar collector. (December 2022) - Zafar, Muhammad Faizan; Ali, Muzaffar; Akhter, Javed; Kaleem, Muhammad; Sheikh, Nadeem Ahmed
Highlights: MgO and Al2 O3 nanofluids are used with water and ethylene glycol as base fluids. Stability and characterization of nanofluids with different concentrations are determined. Thermal performance of CPC collector is experimentally assessed using nanofluids. Maximum efficiency enhancement of 25% is achieved at specified test conditions. Abstract: Solar energy is the primary renewable and globally freely available resource of clean energy. Various types of solar collectors are used to extract thermal energy for low to medium temperature applications. Water and Ethylene Glycol, generally used as heat transfer fluids in such collectors, have low thermal conductivity which negatively impacts their performance. In this study, synthesis, stability analysis, characterization and thermal performance of metallic oxides-based nanofluids in a low concentration compound parabolic concentrating (CPC) solar collector is presented. Nanofluids with three volumetric concentrations (0.025, 0.05, 0.075 %) of MgO and Al2 O3 nanoparticles are synthesized using water and Ethylene Glycol as base fluids. Two-step method is used to prepare colloidal suspensions with the help of magnetic stirring, shear homogenization, and ultrasonication process. For stability analysis, zeta potential measurements are carried out at 25 °C and 65 °C. Al2 O3 /EG and MgO/EG have shown zeta potential of −33.45 mV and +32 mV respectively at 25 °C. Maximum thermal conductivity enhancement of 33.80 % is noted for Al2 O3 /H2 O while dynamic viscosity enhancement of 11.83 % is recorded for MgO/EG nanofluids with 0.075 %. volumetric concentration. Thermal performance of a stationary CPC collector is also evaluated using prepared nanofluids at flow rates of 0.02 kg/s and 0.015 kg/s. The experimental results show that a maximum temperature difference of 8.93 °C is achieved using Al2 O3 /H2 O nanofluid with a volumetric concentration of 0.075 % at a flow rate of 0.015 kg/s. Maximum thermal efficiency enhancement of 25.03 % and 24.02 % is recorded for MgO/EG nanofluid with 0.075 % volumetric concentration at flowrate of 0.02 kg/s and 0.015 kg/s, respectively.